When clicking becomes uncontrollable: The moderating role of fear of missing out and perceived enjoyment - Elia Ardyan; Gracela Marisa Sanapang; Manuel Goncalves (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
Indonesia's live-stream-selling business is experiencing growth as more social media vendors are embracing live-streaming platforms. Online live selling has rendered purchasers vulnerable to compulsive purchasing and the dopamine trap, as it generates a feeling of exhilaration and social coercion. This research investigates the moderating effects of fear of missing out (FOMO) and perceived satisfaction on the relationship between the perceived usefulness of live streaming and online compulsive buying activity. The respondents in this study were 154 people who had watched live streaming of social commerce and carried out online compulsive buying activities. This study uses convenience sampling as a technique to determine the sample. Each question item is assessed using seven scales. This study uses structural equation modeling partial least squares to analyze the data. This research shows that the influence of the perceived usefulness of live streaming can increase online compulsive buying activity. Apart from that, the critical role of FOMO and perceived enjoyment can moderate the influence of the perceived usefulness of live streaming on online compulsive buying activity. This study makes a valuable contribution to the field of dual process theory. This study also offers practical implications for managers, highlighting the undeniable impact of the fear of missing out on individuals who find satisfaction in live streaming. This fear intensifies their anxiety and desire to stay connected with others' activities, especially if they believe that participating in live streaming is crucial for maintaining relationships or staying informed.